New Face for Chromatin‐Related Mesenchymal Modulator: n‐CHD9 Localizes to Nucleoli and Interacts With Ribosomal Genes. Issue 9 (26th May 2015) - Salomon‐Kent, Ronit; Marom, Ronit; John, Sam; Dundr, Miroslav; Schiltz, Louis R.; Gutierrez, Jose; Workman, Jerry; Benayahu, Dafna; Hager, Gordon L.
Abstract : Mesenchymal stem cells' differentiation into several lineages is coordinated by a complex of transcription factors and co‐regulators which bind to specific gene promoters. The Chromatin‐Related Mesenchymal Modulator, CHD9 demonstrated in vitro its ability for remodeling activity to reposition nucleosomes in an ATP‐dependent manner. Epigenetically, CHD9 binds with modified H3‐(K9me2/3 and K27me3). Previously, we presented a role for CHD9 with RNA Polymerase II (Pol II)‐dependent transcription of tissue specific genes. Far less is known about CHD9 function in RNA Polymerase I (Pol I) related transcription of the ribosomal locus that also drives specific cell fate. We here describe a new form, the nucleolar CHD9 (n‐CHD9) that is dynamically associated with Pol I, fibrillarin, and upstream binding factor (UBF) in the nucleoli, as shown by imaging and molecular approaches. Inhibitors of transcription disorganized the nucleolar compartment of transcription sites where rDNA is actively transcribed. Collectively, these findings link n‐CHD9 with RNA pol I transcription in fibrillar centers. Using chromatin immunoprecipitation (ChIP) and tilling arrays (ChIP– chip), we find an association of n‐CHD9 with Pol I related to rRNA biogenesis. Our new findings support the role for CHD9 in chromatin regulation and association with rDNA genes, in addition to its already known function in transcription control of tissue specific genes. J. Cell. Physiol. 230: 2270–2280, 2015. © 2015 Wiley Periodicals, Inc.